Conservative management for patients with chronic kidney disease refusing dialysis - Castro,Manuel Carlos Martins (2019)
ABSTRACT Estimates suggest that 20-30% of the deaths of patients with chronic kidney disease with indication to undergo dialysis occur after refusal to continue dialysis, discontinuation of dialysis or inability to offer dialysis on account of local conditions. Contributing factors include aging, increased comorbidity associated with chronic kidney disease, and socioeconomic status. In several occasions nephrologists will intervene, but at times general practitioners or family physicians are on their own. Knowledge of the main etiologies of chronic kidney disease and the metabolic alterations and symptoms associated to end-stage renal disease is an important element in providing patients with good palliative care. This review aimed to familiarize members of multidisciplinary care teams with the metabolic alterations and symptoms arising from chronic kidney disease treated clinically without the aid of dialysis.